Care cascade for patients with opioid use disorder and serious injection related infections. Issue 1 (30th November 2021) - Upadhyaya, Anand; Marks, Laura R.; Schwarz, Evan S.; Liang, Stephen Y.; Durkin, Michael J.; Liss, David B.
Abstract: Objectives: To define the care cascade for patients with serious injection drug use related infections (SIRI) in a tertiary hospital system and compare outcomes of those who did and did not participate in an opioid use disorder (OUD) treatment referral program. Methods: The medical records of patients admitted with both OUD and SIRI including endocarditis, osteomyelitis, septic arthritis, epidural abscess, thrombophlebitis, myositis, bacteremia, and fungemia from 2016-2019 were retrospectively reviewed. Patient demographics, clinical covariates, 90-day readmission rates, and outcomes data were collected. We compared data from those who were successfully referred to outpatient care through Engaging Patients in Care Coordination (EPICC), a peer recovery specialist-run OUD treatment referral program, to those who did not receive outpatient referral. Results: During the study period 334 persons who inject opioids were admitted with SIRI. Fourteen admitted patients died and were excluded from the analysis. The all-cause readmission rate was lower among patients referred to the EPICC program (18/76 [23.7%]) compared to those not referred to EPICC (100/244 [41.0%]) (OR 0.44; 95% CI 0.25–0.80). Conclusion: An OUD care cascade evaluation for patients with SIRI demonstrated that referral to peer recovery services with outpatient OUD treatment was associated with reduced 90-day readmission rate.